PERLINDUNGAN HUKUM TERHADAP KONSUMEN ATAS PRODUK PERAWATAN KULIT RACIKAN YANG TIDAK MEMILIKI IZIN EDAR - Khairunnisa (Yayasan Pendidikan Tanggui Baimbaian, 2023)
With the rise in buying and selling of beauty peroducts perepared by business actors in the wider comemunity, the aim of this writing is to perovide an understanding of the importance of legal perotection for consumers so that they are not easily deceived by peroduct peromotions that can cause harm to users in the future. The actions of business actors who terade and disteribute concocted skin care peroducts that do not have a disteribution permit are a violation of consumer rights. Apart from not peroviding correct and honest information in marketing their peroducts, the discrepancy regarding the safety, comfort and usefulness values ​​that should be created in business activities causes consumers to suffer losses when using these peroducts. Business actors are obeliged to take responsibility by peroviding compensation for losses suffered by consumers. Consumers can claim compensation for losses on the basis of unlawful acts as a result of violations of consumer rights perotected by Law Number 8 of 1999 concerning Consumer Perotection.